ANALISIS GENDER MENURUT PROFIL AKSES DAN KONTROL PETANI WIJEN (Sesanum indicum, L) DI KECAMATAN BAIG KABUPATEN SUKOHARJO - Dessy Dessy; Supanggyo Supanggyo; Retno Setyowati (Universitas Sebelas Maret, 2005)
The goal of this research are to see the differences of time productive activity, proportion a/location, domestic and public society between men and women; the differences of access and control on resources between men and women; also the relationship between norm and time activity allocation on sesame farmer's access and control. Most ofthe men and women responden on the 45-54 age range. For the education level , male farmer was on higher level than women farmer. The norm on the sesame farmer society at Baki district sukoharjo Regency was patrialkal and egalitarian. Between male and women sesame farmer there are differences for the time activity allocation. Much more male sesame farmer spent the time for productive activity, whereas women spent the time for domestic activity. Women access on productive resources was lower than male, but for the control there is no differences. There is no differences on access and control on domestic and public society resources.